Effect of Molybdenum Disulphide Thin Films on Enhancing the Performance of Polycrystalline Silicon Solar Cells - Rajasekar Rathanasamy; Gobinath Velu Kaliyannan; Santhosh Sivaraj; Essakkiappan Muthiah; Abdul Azeem Ajmal Khaan; Dharmaprakash Ravichandran; Md. Elias Uddin (International Journal of Photoenergy)
This research work focuses on augmenting the power conversion efficiency of the polycrystalline silicon solar cell with the aid of antireflection coating (ARC) of synthesized molybdenum disulphide (MoS2). The sol-gel technique and electrospraying method were preferred for synthesizing and depositing MoS2 as transparent thin films on the surface of the solar cells. The optical, electrical, structural, and thermal properties of the coated solar cells were analyzed for understanding the influence of the MoS2 coating. Five different samples (A-II, A-III, A-IV, A-V, and A-VI) were coated with varying coating time. Among them, 120 min coated sample experienced a maximum power conversion efficiency (PCE) of 17.96% and 18.82% under direct sunlight and neodymium light with resistivity as low as 2.79×10−3 Ω−cm. The investigation of optical properties of the coated solar cells revealed a maximum transmittance of 93.6% and minimum reflectance of 6.3%, achieved for A-IV sample in the visible UV spectrum. Sample A-IV showed prominent results in the temperature analysis with temperatures as low as 38.9°C in uncontrolled and 43.2°C in controlled source environments. The results from various analyses proved that MoS2 was an appropriate material for an antireflection coating to enhance the performance of polycrystalline solar cell.